Konjugasi pada Bahasa Sikka Krove di Kabupaten Sikka Nusa Tenggara Timur - Bertholomeus Jawa Bhaga (Jurnal Bahasa dan Sastra, 2021)
Sikka’s verbs have different features from other regional languages in their application in sentences. This is because the Sikka verbs undergo a conjugation process, which is a change in the form of the verb based on the persona pronoun that precedes it. Based on observation during the language practice of speakers of this language, it can be seen that certain verbs, namely 'eat' and 'drink' in Sikka language, are unique, namely the existence of an inflection process that is more conical in conjugation. This research aims to describe the various patterns formed as a conjugation process. This type of research is qualitative, that the data is a description using verb words. The method used in this research is descriptive qualitative method, namely analyzing descriptive data by describing various conjugation patterns that occur in the Sikka language. The result obtained is a form of conjugation based on the subject followed by the verb "eat" and "drink" in the Sikka language. That it turns out that there is a change in the form of the verb due to a change in the subject. Meanwhile, the time form and other forms were not found in this study.